Pengaruh Penggunaan Media Film Terhadap Peningkatan Keterampilan Menulis Teks Tanggapan di SMP Negeri 4 Madiun - Etika Dwi Cahyani; Eni Winarsih; Sri Andayani (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Through the research activities carried out, students are invited to change their views, so that writing responses becomes a fun learning activity. The aim of the research was to see the effect of using film media on improving response text writing skills. In this activity, the type of research is classroom action research (PTK), then the method used is qualitative and quantitative descriptive analysis with the target subject being class VII D students at SMP Negeri 4 Madiun. Based on data sources using primary data obtained from research subjects through initial stage collection techniques of tests, interviews and observations. Checking the validity of the data uses the results of students' grades by considering the increase in learning outcomes in each phase of the cycle starting from the pre-cycle, cycle I and cycle II stages. Analysis of research data carried out qualitative and quantitative analysis. The results of the research show that there is an influence of the use of film media on response text writing skills which has increased starting from the initial pre-cycle results with a percentage of 46.87% up to the first cycle stage showing quite good improvement with a completion percentage of 56.25% and cycle activities. II with a completion score percentage of 84.37% which shows an increase.